Rede de cooperação: proposta de configuração entre escolas sinodais da região noroeste do RS - Nüske, Mauro Alberto (2006)
The growth of competition, the opening of the markets and the expansion of the education section provide new challenges in the administration of the school institutions. There is also the aspect of quality improvement of public institutions, because of the increase of governments' investments in their education system. According to this reality, it is necessary to change some concepts, which consider that companies or institutions of the same branch of performance should be competitive; on the contrary , they should adopt strategies and united actions, for acting in the Cooperation Net . For Sinodal schools of the Northwest Region of Rio Grande do Sul state, this need is evidenced, reasons for which this present research looked for analyzing the strategical-enterprise factors of competitiveness of 5 Sinodal schools of the Northwest Region of RS, through the application of researches among their managers and among the external customers of their schools. In the methodology, the approach method and procedures were used, and techniques of direct and indirect documentation. The study was descriptive, and the approaches used in the research were the qualitative and the quantitative. Among the researched aspects, it was looked for evaluating the largest "gaps" (intervals) with the research of the managers and the research with the external customers (parents or responsible), which were identified and analyzed. It was also evaluated the aspects considered as load points and about weak points of the Sinodal schools, in each school, and jointly. In the analysis of the group of schools, it is ended that the same ones influence their customers, mainly, for the quality of the teaching and the teachers' qualification, for the pedagogic and curricular proposal, for the efficiency of the teaching and for the extracurricular options of courses. In the managers' optics, they judge that their external customers opt for the school that is driven by them, mainly, for the efficiency and quality of teaching and the teachers' qualification, for the preference of private school, for the extra-curricular options of courses, for the pedagogic and curricular proposals and for community insert. The result of the analyses addresses for which strategic-business factors of competitiveness need to be potentiated, so that those schools can adopt, hereafter, strategies and actions as Cooperation Net.